Optimization Corporate University through KMS and LMS Integration for Organizational Development in the Digital Transformation Era - Slamet, Slamet; Sartika, Ika (JUPE : Jurnal Pendidikan Mandala, 2025)
Digital transformation requires organizations to strengthen their learning and knowledge management capabilities in a structured, targeted, and consistent manner. In this regard, the integration of the Knowledge Management System (KMS) and the Learning Management System (LMS) is strategic in strengthening the role of Corporate Universities (Corpu) as centers for human resource competency development and drivers of organizational change. The purpose of this study is to examine in depth the optimization of KMS and LMS integration in supporting digital organizational development and to analyze the strategic role of Corpu in the organizational transformation process. Using a qualitative descriptive approach through literature review, this study examines various relevant academic sources to evaluate concepts, models, and best practices that have been implemented in various organizations. The research results show that KMS and LMS integration can form an integrated and collaborative digital learning ecosystem, strengthen knowledge management flows, and increase the effectiveness of organizational learning. Corpu plays a key facilitator in synergizing digital systems by aligning the organization's strategic needs with HR competency development. This study provides theoretical contributions to the development of digital organizational learning models and recommends practical implications for policymakers and learning system managers to adopt technology integration sustainably.